Assessments scales for the evaluation of health-related quality of life in Parkinson's disease, progressive supranuclear palsy, and multiple system atrophy: a systematic review - Maiuolo, Maria Lucia; Giorgini, Roberto; Vaccaro, Maria Grazia; Facchin, Alessio; Quattrone, Andrea; Quattrone, Aldo (Frontiers in Psychology, 2024)
Background. The concept of well-being is an expansive and intricate concept, making it challenging to articulate and establish a precise definition. Similarly, the instruments employed to assess well-being are complex and multifaceted. Hence, it is more appropriate to designate the notion of well-being as Health-Related Quality of Life" (HRQoL). Indeed, it is the central point of many measures used to assess the feeling of well-being. The objective of this review was to identify the most utilized tools for evaluating Health-Related Quality of Life in individuals with Parkinsonism. This group of movement disorders negatively impact quality of life due to the intricate interplay of symptoms, socio-demographic characteristics, and psychological factors. The main aim is to assess the psychometric properties of these measure, in terms of validity and reliability. Methods. A literature review was performed, encompassing research on the assessment of health-related quality of life in connection to symptoms of Parkinsonism. This review covered all studies that examined Health-Related Quality of Life utilizing evaluation scales, exams, or self-reported questionnaires. The literature review was conducted using the databases Scopus, Web of Science and the search engine PubMed, to identify papers from 1996 to 2023. Only the records that assessed Health-Related Quality of Life in individuals with Parkinson's disease and Parkinsonisms were chosen for evaluation. Results. A total of 393 records were examined, and 8 tools have been selected as the most used in the evaluation of Health-Related Quality of Life. Discussion. From results emerge a paucity of knowledge on the Latent Structure and Measurement Invariance of Health-Related Quality of Life measurements may have a significant influence on the interpretation of test outcomes.Moreover, there is not a distinct divergent validity between Health-Related Quality of Life assessments and tests used as a predictor of it; this could be a significant limitation that influences construct and criterion validity of Health-Related quality of Life measures.